ChemInform Abstract: Synthesis of N‐Cbz‐Substituted β3‐Amino Ketones Utilizing 4‐Substituted 1, 3‐Oxazinan‐6‐ones. Issue 33 (25th July 2013) - Sleebs, Brad E.; Nguyen, Nghi H.; Hughes, Andrew B.
Abstract The approach to the synthetically important chiral β‐amino ketones involves diastereoselective acylation of 1, 3‐oxazinan‐6‐ones followed by acidic decarboxylation.